Living in a material world - Barker, Melinda; Games, Martin Hughes (Bristol : BBC-TV Production [production company] ; London : BBC Education & Training [distributor], 1994)
Describe on the nature shapes and designs. Different types of rock such as granite give different geology shapes
Produced by BBC-TV Production in association with Lionheart Television International
Copy available in DVD format
Film editor, Martin Elsbury
Narrator: Richard Jobson
Keywords: Rock-forming mineral; Shape theory (Topology); Minerals